CORRELATION OF ENDOSCOPIC FINDING WITH HISTOLOGICAL, DIAGNOSIS IN GASTRITIS - Manan, Alamzeb; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: Twenty-five (14 males and 11 female) gastritis cases diagnosed on endoscopic examination revealed some form of inflammatory lesion of gastric mucosa. All the cases were biopsied for histological confirmation of diagnosis. Nineteen of 25 had histological evidence of the disease while 6 showed no histological changes. Thus in about 76% cases there was positive correlation between endoscopic and histopathological diagnosis.